ISLAM AND DEMOCRACY: AGHESTAN’S PROGRESS TOWARD DEMOCRACY - KAZIMOVA, Raziat; KOTELENKO, Dmitri (CENTRAL ASIA AND THE CAUCASUS, 2004)
The elections to the State Duma of the Russian Federation that took place on 7 December,2003 revived an interest in the nearly forgot-ten issues of the alignment of political forces in Daghestan and in what sort of democracy people would like to see there. One should bear in mind that United Russia, the so-called party of power, scored the most convincing victory in the republic (66.3percent of those who came to the polls).1 The Communists with 17.7 percent of the votes suffered a crushing defeat—it was nearly half of what they had won in 1999. It should be said that another striking result of the same elections is no less interesting.